WESTERN BALKANS COUNTRIES AND THEIR POSITION AS CONTRIBUTORS AND CONSUMERS IN THE CONTEMPORARY EUROPEAN SECURITY ARCHITECTURE - Spasov, Aleksandar (Ministry of Defence of the Republic of North Macedonia, 2024)
Western Balkans countries, geographically part of southeastern Europe, politically remain on the periphery of Europe. The European integration of the Western Balkans countries although confirmed as one of the strategical priorities of the European Union since the Thessaloniki Summit in 2003, more than two decades after remains an unfinished project with exception of the membership of Croatia. The stalemate in the European integration of the Western Balkans countries beside the political and economic issues is also an issue of geopolitical and security nature, both for the European Union and the Western Balkans countries. This article deals with the geopolitical and security significance of the Western Balkans countries for the European security architecture as well as with the geopolitical and security consequences resulting from stalemate in the process of the European integration of the mentioned countries. The focus of the article is on the possibilities for malign influence that the stalemate creates for third, extra regional actors, hostile to the European Union and, on a long term, to the democratic development of the Western Balkan countries.
Keywords: Western Balkans, European Union, European integration, Geopolitics, Security.